The Impact of Cloud Computing on Business Scalability in the Indian IT Sector - AKRAM KHAN, MR. WASIM (International Journal of Multidisciplinary Research and Studies, 2024)
Cloud computing has made a big difference in how companies can grow and keep up with changing markets. In simple terms, cloud computing means that businesses can get IT resources like storage, computer power, and software through the Internet when they need them, instead of buying and managing their own equipment. This means companies don’t have to spend a lot of money upfront on things like big data centers or servers. Instead, they pay for only what they use. This is very helpful in India’s IT sector, which is growing quickly and going digital at a fast pace. Cloud computing is helping companies in India by making their work easier, reducing costs, and allowing them to scale or grow whenever needed.